The role of the trainer in the continuing education process: trainers or informants (Research, Society and Development, 2020)
The aim of this research is to understand the role of the trainer in the context of continuing teacher education, highlighting its importance in the process. To carry out the studies and substantiate the article, we seek to dialogue with several renowned authors, such as: Nóvoa, Prada, Saveli, Perrenoud, Weisz, among others. For the methodology was adopted a field research, of qualitative nature with interpretative nature, seeking to understand the research objective and to show that the trainer is the most important subject in the construction of meaningful formation for the teaching and learning process of the teacher and for its role in the construction of knowledge necessary for teaching. The research was conducted with 10 (ten) subjects, teachers of a kindergarten center in Campo Verde - MT. The choice of this field of research is justified by the presence of the continuing education process in the institution. The instrument used for data collection was a questionnaire, containing 06 (six) open questions. The results show that one hundred percent of teachers recognize the importance of the trainer in the continuing education process, making it clear that they can make countless contributions to classroom praxis; They also describe that to be a trainer is not enough to be a teacher and narrate that the profession of trainer requires specific characteristics to develop a good performance, such as: know how to listen, be dynamic, companion, have experience, among others. Thus, the research data contributed to the achievement of its objectives, making clear the information raised and the contributions of the trainers in the context of education.